Sequestration of Cadmium Ions from Aqueous/ Electroplating Wastewaters Using Chitosan: A Review - Muthulakshmi , A. N.; Anuradha, J. (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
The present study aimed to determine sequestration of Cadmium Ions from Aqueous/ Electroplating Wastewaters Using Chitosan. Due to its serious harmful effects on human, animals, and plants, the removal of Cd2+ ions from wastewaters is receiving a lot of attention from both environmental and economic perspectives. Due to its low cost and high concentration of amino and hydroxyl functional groups, the crustacean waste known as chitosan has attracted considerable attention as a powerful biosorbent. The chemical changes that result in chitosan derivatives, chitosan grafting, and chitosan composites have been thoroughly studied and widely reported in the literature. The purpose of this study is to provide an overview of the sorption performance of chitosan and its derivatives in the removal of Cd2+ ions from synthetic waters and electroplating effluents. A comparison on the chitosan derivatives prepared by five different methods as reported by researchers (thiocarbomyl, PVA blend, xanthate, Nano based and grafting) and an outline of their potential applications in the adsorption of Cd2+ ions are dealt in this paper. Amongst the mentioned composites reported, chitosan grafted with y- cyclodextrin is found to possess better chelating ability in chelating Cd2+ ions.